Growth of hydrothermally stable meso-porous silica structure interconnected around micro-porous zeolite crystals - Kinage, Anil K.; Prashar, Atul K.; Berlier, Gloria; Chaturvedi, Rajiv K. (Materials Characterization, 2011)
The growth of hydrothermally stable ordered meso-porous silica with M41S type structure interconnected around zeolite crystals was achieved from seeds normally nucleating the crystallization of micro-porous zeolite. The solid state NMR and FT-IR showed species like Si(OSi)(3)OH and Si(OSi)(2)(OH)(2) (or Q(3) and Q(2) sites, respectively) are formed during first hydrothermal treatment with surfactant and NaOH. These species and surface silanol group of zeolite crystal condense to give meso-porous silica structure interconnected around zeolite crystal during re-crystallization at lower pH. Resulting meso-micro-porous hybrid material is found to be highly active, selective and stable in the synthesis of 2-(phenylamino) ethanol from aniline and ethylene carbonate compare to parent ZSM-5 and pure MCM-41. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Hydrothermal stability; Interconnected meso-porous silica; Meso-micro hybrid material; Synthesis of amino alcohol